Circulation of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Mycobacterium tuberculosis strains in Mexico - Vazquez-Chacon, Carlos A.; Martinez-Guarneros, Armando; Campos, Susana Balandrano; Herrera, Julieta Luna; Bäcker, Claudia; Rossi, Livia Maria Gonçalves [UNESP]; Ruiz-Tovar, Karina; Fonseca-Coronado, Salvador; Carpio-Pedroza, Juan C.; Vaughan, Gilberto; Escobar-Gutierrez, Alejandro (Science Publications, 2015)
Emergence of Extensively Drug-Resistant (XDR) Tuberculosis (TB) is an important public health problem worldwide. In Mexico, the extent of circulation of XDR-TB strains is unknown. Here, the drug-resistance patterns of TB isolates collected in Mexico between 2006 and 2008 were analyzed. Among 137 TB isolates, (58%) were classified as MDR exclusively, (33%) were Pre-XDR and (9%) were assigned as XDR. The results confirmed the circulation of Pre-XDR and XDR-TB in Mexico. Surveillance and drug-susceptibility testing should be improved in Mexico to monitor the circulation of XDR strains.
Keywords: MDR; Mexico; Pre-XDR; Tuberculosis; XDR